Does the perceived risk of punishment deter criminally prone individuals? Rational choice, self-control, and crime - Wright, Bradley R. Enter; Caspi, Avshalom; Moffitt, Terrie E.; Paternoster, Raymond (Journal of research in crime and delinquency, 2004)
Society's efforts to deter crime with punishment may be ineffective because those individuals most prone to commit crime often act impulsively, with little thought for the future, and so they may be unmoved by the threat of later punishment. Deterrence messages they receive, therefore, may fall on deaf ears. This article examines this issue by testing the relationship between criminal propensity, perceived risks and costs of punishment, and criminal behavior. The authors analyzed data from the Dunedin New Zealand Study, a longitudinal study of individuals from birth through age26N = 1,002. They found that in fact, deterrence perceptions had their greatest impact on criminally prone study members